Psychiatrische Komorbiditäten bei tabakbedingten Störungen = Psychiatric comorbidities with tobacco-related disorders - Mühlig, Stephan; Hoch, Eva (Der Nervenarzt, 2016)
The coincidence of tobacco smoking and psychiatric disorders is of great epidemiological and therapeutic importance. Tobacco smoking by people with mental disorders leads to disproportionately high somatic health risks, an adverse clinical course, poorer clinical outcomes and reduced quality of life (QoL). The etiological causes of the high comorbidity between smoking and mental disorders are still unclear: currently, tobacco smoking is discussed as being either the consequence or contributory cause of psychological disorders or both disorders share common antecedents and interactions. Psychiatric patients are motivated to quit and smoking cessation is not generally less effective with smokers with mental disorders than with mentally healthy individuals. Specific smoking cessation programs in the inpatient and outpatient settings are time-consuming and complex but effective. Within the framework of the current S3 guidelines the international evidence has been updated and transformed into treatment guidelines following an elaborate consensus process. Basically the same interventional measures should be used as with mentally healthy individuals; however, smokers with a psychological comorbidity often need more intensive adjuvant psychotherapeutic interventions and often need pharmaceutical support, (bupropion, varenicline and nicotine replacement therapy). Due to the overall unsatisfactory findings the treatment guidelines are partially based on clinical consensus decisions. In this field, a considerable need for research has been determined.
Gesehen am 31.10.2019
Online publiziert: 23. November 2015